Low‐Temperature Processed Nanostructured Rutile TiO2 Array Films for Perovskite Solar Cells With High Efficiency and Stability. Issue 2 (28th December 2017) - Wu, Shufang; Cheng, Chi; Jin, Jingpeng; Wang, Jinming; Peng, Tianyou
Abstract : The rutile TiO2 array (RTA) films consisting of vertically oriented nanoneedles and/or nanosheets are grown on a fluorine‐doped tin oxide (FTO) glass substrate via a chemical bath deposition (CBD) process at 70 °C, and are utilized as electron transport layer (ETL) for CH3 NH3 PbI3 ‐based perovskite solar cells (PSCs). The morphology and microstructure of the RTA films can be tuned by varying the CBD time. A mixed nanoneedles/nanosheets array film (∼250 nm thickness) derived from 60 min CBD process achieve a power conversion efficiency (PCE) up to 15.4% with reduced hysteresis, improved reproducibility, and stability as compared to those PSCs based on traditional mesoscopic‐TiO2 or planar‐TiO2 ETLs, which is due to the lower charge recombination, more efficient hole‐blocking, and electron transport. After aging and storage in the dark, the optimal PSC exhibits a slightly improved PCE (16.3%), which is the highest one among those CH3 NH3 PbI3 ‐based PSCs fabricated with low‐temperature processed RTAs reported previously. This work is the first example of vertically oriented nanosheets and/or nanoneedles RTA film grown on a conductive glass to serve as ETL of PSC, and the low‐temperature procedure of the RTA film paves a promising low‐cost way for fabricating large‐scale PSCs. Abstract : A low‐temperature processed nanoneedle/nanosheet rutile TiO2 array film is fabricated as ETL of CH3NH3PbI3‐based PSCs for the first time. The rutile TiO2 array can act as a hole blocking layer and an electron transport layer to efficiently improve the photovoltaic performance and the stability of the PSCs.